Correlation between Interleukin-17 Levels with C-Reactive Protein and Neutrophil Lymphocyte Ratio in Sepsis - Dwi Retnoningrum; Muchlis Achsan Udji Sofro; Setyo Gundi Pramudo; Satrio Adi Wicaksono; Andaru Dahesihdewi (Journal of Biomedicine and Translational Research, 2022)
Background: Sepsis is a condition in systemic infection associated with organdysfunction. Interleukin-17 is a pro-inflammatory cytokine produced by Th-17 cells. C-reactive protein and neutrophil-lymphocyte ratio (NLR) have been widely used asmarkers of inflammation. The relationship between IL-17 as a proinflammatorycytokine with CRP and NLR has not been reported.Objective: This study aims to prove the correlation between IL-17 with CRP and NLRin septic patients.Methods: Analytical observational study with a cross-sectional approach was carriedout on 40 septic patients in July–December 2020. IL-17 levels were obtained by theELISA method while CRP levels were obtained using the immunoturbidimetric method.NLR was the result of dividing the absolute number of neutrophils and lymphocytesfrom the automatic hematology analyzer. Correlation between variables was performedusing Spearman correlation test.Results: The median levels of IL-17, CPR, and NLR were 363.55 (11.4-1695.80)pg/mL, 13.25 (0.43-53.87) mg/L, and 12.00 (2.26–48.5), respectively. The Spearmancorrelation test between IL-17 levels and CRP obtained p = 0.019, r = 0.37, and NLR p= 0.425, r = 0.13.Conclusion: There is a weak positive correlation between IL-17 levels and CRP inseptic patients. There is no correlation between IL-17 levels and NLR in septic patients.